MOTIVASI MASYARAKAT DALAM MEMILIH PEMIMPIN (Studi Kasus Pada Pemilihan Kepala Desa Hargomulyo, Gedangsari, Gunungkidul) - Indri Astuti; Widodo Widodo (Aliansi : Jurnal Manajemen dan Bisnis, 2019)
Society always hunger for a leader which can be expected by its protecting people is more when commutation moment hence people surely hope the leader which will more baih in holding governance wheel. At authors opportunity start from survey later; then communicate with the society of either through direct and also through/passing media social later; then do/conduct this research with the descriptive method qualitative Hence at this opportunity is writer will pare and explain how society motivation in chosening leader? Highest expectation 31% improving people earnings, equal to 15% that is hold responsible. equal to 13%, People 11%, 11%, in activity RT / rw 8%, Cleanness 5%, 3%, and Agamis 3%. Suggestion from writer that society of if wishing happy peaceful and prosperous life and also have to and is obliged to remember the Allah SWT. by diligent of religious service. Because place Allah curtsey and place ask. If that leader as medium, because good leader is which religious.